(untitled) (Journal of Biomedical Investigation, 2022)
Background: Community-dwellers are often in need of physiotherapy and rehabilitation for non-communicable disease conditions particularly chronic low back pain and cerebrovascular accidents. However, the access to physiotherapy and rehabilitation in rural areas is grossly inadequate. Aim of the study: This study aimed to ascertain the level of knowledge, attitude and practice of community physiotherapy amongst physiotherapists in southeastern Nigeria. Materials and Methods: In this cross-sectional study, a total of 81 physiotherapists possessing at least 2 years of clinical experience were consecutively sampled from 10 conveniently selected hospitals in the 5 southeastern states. We assessed participants using a validated self-administered Knowledge, Attitude and Practice (KAP) questionnaire. We summarized data using the statistics of percentage, mean and standard deviation. Mann-Whitney and Kruskal-Wallis tests were used to test the influence of selected socio-demographic characteristics on knowledge, attitude and practice of Community Physiotherapy. Spearman rank-order correlation was used to test for the relationship among knowledge, attitude and practice of community physiotherapy. Results: The mean age of participants (females = 57, males =43) was 36.3±6.5 years. Good knowledge (84.30±6.79%) and attitude (84.35±5.85%) and fair practice (74.76±9.33%) of community physiotherapy were observed among the study participants. There were significant correlations among knowledge, attitude and practice of community physiotherapy among physiotherapists (p<0.05). Factors constituting a hindrance to the assimilation of community physiotherapy were poor remuneration and lack of basic social infrastructure. Conclusions: There is good knowledge and a good attitude and fair practice of community physiotherapy among physiotherapists in our settings. Efforts should be made to address the hindrances to community physiotherapy.